2010 : the future of networks. (1994)
Outlines six possible outcomes for the network industry in 2010, from inertia to revolution. Each one will affect computer users and network managers differently. Describes the computing environs and how they came into existence, the key technologies and companies, and how the services are paid for and delivered.
DC